1996
DOI: 10.1007/bf02361156
|View full text |Cite|
|
Sign up to set email alerts
|

Developmental isolation and subsequent adult behavior ofDrosophila paulistorum. III. Alternative rearing

Abstract: We have been utilizing members of the Drosophila paulistorum complex of semispecies to study the development of adult discriminatory behavior. In this study, three rearing methods were used to examine the effects of previous exposure to heterosemispecifics on reproductive isolation among the various semispecies. Experimental flies were exposed to heterosemispecifics by one of three methods: exposure to airborne heterosemispecific stimuli from egg through sexual maturity, physical contact with heterosemispecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Increasing this time, as is done in many studies (e.g., 3-4 h in Santibafiez and Waddington 1958; 90 min in Kilias et al 1983; 60 min in Lambert and Henderson 1986), increases the probability of surpassing the critical number of matings and obtaining spurious isolation results. In fact, the use of long observation times would lead to almost 100% of matings (for instance, Ehrman and Parsons 1980;Kim et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing this time, as is done in many studies (e.g., 3-4 h in Santibafiez and Waddington 1958; 90 min in Kilias et al 1983; 60 min in Lambert and Henderson 1986), increases the probability of surpassing the critical number of matings and obtaining spurious isolation results. In fact, the use of long observation times would lead to almost 100% of matings (for instance, Ehrman and Parsons 1980;Kim et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila paulistorum Dobzhansky & Pavan malesexperimentally isolated during developmentfail to discriminate appropriate mating partners and are as likely to mount males as females; it seems they need experience during development with conspecifics to know who is and is not a potential mate (Kim et al, 1996). Drosophila paulistorum Dobzhansky & Pavan malesexperimentally isolated during developmentfail to discriminate appropriate mating partners and are as likely to mount males as females; it seems they need experience during development with conspecifics to know who is and is not a potential mate (Kim et al, 1996).…”
Section: Ynamtementioning
confidence: 99%
“…However, the possibility of an influence of the conditions encountered in the egg stage on the behavior of the adult flies has been repeatedly demonstrated in a series of experiments by Kim et al (1996). The authors found that mixed culturing of eggs from different semispecies of the Drosophila paulistorum group weakened selectively the mutual attraction of adult females and males from different semispecies.…”
Section: Development and Retention Of Odor Indifferencementioning
confidence: 99%